Estimation of children’s age based on dentition via panoramic radiography in Surabaya, Indonesia - Agung Sosiawan; An'nisaa Chusida; Beshlina Fitri Widayanti Roosyanto Prakoeswa; Arofi Kurniawan; Maria Istiqomah Marini; Beta Novia Rizky; Tito Krisna Gianosa; Najminoor Ramadhani Ridlo; Mumtaz Ramadhani Putra Pesat Gatra; Aspalilah Alias (Dental Journal, 2022)
Background: Age may be estimated using tooth eruption sequence and/or calcification stage. Because many factors may affect the time of eruption, the tooth calcification stage shows higher accuracy than the time of tooth eruption. Demirjian’s and Willems’ methods have been most commonly used for dental age estimation. Both Willems and Demirjian use the calcification stage as an indicator. Studies comparing these methods have shown varied results, as they have been performed on different populations. Purpose: This paper aims to analyse the estimation of children's age based on dentition via panoramic radiography in Surabaya, Indonesia. Methods: This is a cross-sectional study using a purposive sampling method. One hundred digital panoramic radiographs of children between 6 and 15 years that match the inclusion criteria from the Airlangga University dental hospital in Surabaya, Indonesia were evaluated. One researcher analysed estimated dental age (EDA) three times in a one-week time-lapse using Demirjian’s and Willems’ methods. Statistical analysis was carried out using a Paired t-test and Wilcoxon signed-rank test. EDA was calculated using both Demirjian’s and Willems’ methods. Results: The mean chronological age (CA) was 10.57 ± 2.70 for males and 10.73 ± 2.84 for females. The mean difference between CA and EDA using the Demirjian and Willems methods was -0.57 ± 1.17 and 0.10 ± 0.96 for males and 0.58 ± 1.40 and 0.44 ± 0.94 for females. Conclusion: The results suggest that Willems’ method is more precise than Demirjian’s method in males and females and more suitable for children in Surabaya, Indonesia.